The Winchester College (Warden and Fellows' Library) mediaeval manuscripts collection : collection of manuscripts to the year 1600 - Yeats-Edwards, Paul (1600)
Includes early records of Winchester College and the Warden and Fellows' Library, ecclesiastical works, monastic books, and essays, on various subjects such as literature, medicine, and history. Manuscripts from the eighth to sixteenth century.